Single-Server Queue System of Shuttle Bus Performance: Federal University of Technology Akure as Case Study - Ben, Sidiq Okwudili (American International Journal of Multidisciplinary Scientific Research, 2019)
This study has examined the performance of University transport bus shuttle based on utilization using a Single-server queue system which occur if arrival and service rate is Poisson distributed (single queue) (M/M/1) queue. In the methodology, Single-server queue system was modelled based on Poisson Process with the introduction of Laplace Transform. It is concluded that the performance of University transport bus shuttle is 96.6 percent which indicates a very good performance such that the supply of shuttle bus in FUTA is capable of meeting the demand.